Religious freedom of employees in public and private sector workplaces in Malaysia: a comparative study of different jurisdictions - Nik Mahmod, Nik Ahmad Kamal; Mohd Yusoff, Rahmawati; Harun, Azmi; Mohd, Azizah; Che Mohd Salleh, Marhanum; Mohd Noor, Noor Azlan; Islam, Md Asraful (Allied Business Academies publishing, 2022)
This paper examines the extent of religious freedom exercised by the employees in public and private sector workplaces in Malaysia and some of the selected countries of the world. Hence, the objects of this study are to investigate the legal and regulatory frameworks governing religious freedom at workplaces in Malaysia and other selected jurisdictions, to highlight the necessity of religious freedom at workplaces and to suggest some policy recommendations to the government of Malaysia for ensuring effective religious freedom and religious diversity practices at workplaces. The study is conducted applying legal and doctrinal research methodology followed by an analytical approach. Both primary and secondary legal sources are considered in identifying and interpreting data. The study finds that there is no distinct legal instrument in Malaysia to govern religious freedom at workplaces. Here, religious freedom at workplaces is governed by the core laws that deal with religious freedom at large, i.e. the Constitution. It is also observed that ensuring religious freedom at the workplaces increases the productivity of an organization significantly, whereas absolute freedom might also affect the discipline inside the organization. At the end it was recommended that a comprehensive legislation is essential for Malaysia to effectively govern religious freedom at workplaces.